Large electronic wave function extension of the oxygen vacancies on EuO1−x surface. (27th September 2019) - Wang, Aaron; Rimal, Gaurab; Dahnovsky, Yuri; Tang, Jinke; Chien, TeYu
Abstract: EuO1−x thin films deposited by pulsed laser deposition on Si(100) surface is studied by scanning tunneling microscopy and spectroscopy at room temperature. Oxygen vacancies in EuO1−x are visualized through d I /d V mapping and large apparent size of the oxygen vacancies (1.8 nm ± 0.5 nm) are found, which is in favor of the bound magnetic polaron (BMP) model. These apparent sizes are considered as the spatial extension of the electron wave function originating from the oxygen vacancies. It is further argued that this observed electronic wave function might be the precursor of the BMP formation occurring at lower temperatures. Moreover, some of the oxygen vacancies have been found (1) migrating; (2) appearing; and (3) disappearing, indicating the instability of the oxygen vacancies on the EuO surface at room temperature.